Follow-up of patients diagnosed with and treated for tuberculosis in Brazil: financial burden on the household - Borge Loureiro1,2, Rafaela; Molino Guidoni2, Leticia; Carlesso Fregona2,3, Geisa; Maria do Valle Leone de Oliveira4,5, Sandra; Sacramento6, Daniel; dos Santos Pinheiro7,8, Jair; Gomes9, Denise; Leonor Noia Maciel1,2, Ethel (Jornal brasileiro de pneumologia, 2023)
Objective: To evaluate the implications of the proportion of annual family income spent in the pre- and post-diagnosis periods in tuberculosis patients followed for after at least one year after completing tuberculosis treatment in Brazil. Methods: This was a cross-sectional study of tuberculosis patients followed for at least one year after completing tuberculosis treatment in five Brazilian capitals (one in each region of the country). Results: A total of 62 patients were included in the analysis. The overall average cost of tuberculosis was 283.84 Brazilian reals (R$) in the pre-diagnosis period and R$4,161.86 in the post-diagnosis period. After the costs of tuberculosis disease, 71% of the patients became unemployed, with an overall increase in unemployment; in addition, the number of patients living in nonpoverty decreased by 5%, the number of patients living in poverty increased by 6%, and the number of patients living in extreme poverty increased by 5%. The largest proportion of annual household income to cover the total costs of tuberculosis was for the extremely poor (i.e., 40.37% vs. 11.43% for the less poor). Conclusions: Policies to mitigate catastrophic costs should include interventions planned by the health care system and social protection measures for tuberculosis patients with lower incomes in order to eliminate the global tuberculosis epidemic by 2035-a WHO goal in line with the United Nations Sustainable Development Goals.